Proposed Marketing Strategy to Strengthen Herbal Patient Loyalty: (Case Study at RSU Holistic Purwakarta) - Fania Qinthara Azka; Ilma Aulia Zaim (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Healthcare service is one of the most important industries in Indonesia. Over the past years, public interest in traditional and herbal medicine has increased, especially after the COVID-19 pandemic. RSU Holistic Purwakarta is one of the pioneers of integrative hospitals in Indonesia that offers herbal inpatient services. However, the hospital is currently experiencing a significant decrease in herbal inpatient visits, which is also reflected in its low bed occupancy rate. Based on preliminary research and problem identification, the main issue found is the declining patient loyalty towards the hospital's herbal services. The objective of this research is to formulate a marketing strategy to strengthen herbal patient loyalty and identify which service quality factors influence patient satisfaction and loyalty. This study applies a quantitative and qualitative approach. The quantitative method is conducted through a survey distributed to 155 herbal inpatients, and the data were analyzed using Structural Equation Modeling (SEM) via SmartPLS. The qualitative method includes interviews with the hospital’s management and marketing team to explore internal service issues and market behavior. The findings show that service quality on the people dimension (reliability, responsiveness, and empathy) has a significant influence on patient satisfaction (R² = 0.696), and satisfaction significantly affects patient loyalty (R² = 0.685). The p-values for all constructs are <0.05, confirming the acceptance of all hypotheses. Interviews also identified inefficiencies such as late doctor attendance. Based on the internal and external analysis using the 7P Marketing Mix, PESTEL, and Porter’s Five Forces frameworks this research proposes a marketing strategy. The result is a TOWS matrix that provides actionable strategies, such as strengthening people-based service quality, enhancing integrated communication efforts, and positioning RSU Holistic as a leading herbal and tourism-based hospital. This study contributes academically and practically by emphasizing the role of marketing strategy in strengthening loyalty in the healthcare industry.